2021
DOI: 10.1111/and.14237
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the reactive oxygen species in spermatozoa during liquid storage of boar semen and its correlation with sperm motility, free thiol content and seasonality

Abstract: Artificial insemination (AI) with liquid-stored semen is a globally accepted method (an effective method) of breeding pigs (Johnson et al., 2000). In Western Europe, ≥90% of sows have been bred by AI for ≥20 years (Rodríguez-Gil & Estrada, 2013), whereas in Japan, it is finally becoming widespread at 60% range, according to the Japan Pork Production Association (https://jppa.biz/jppa-docum ent/). The outcome of AI is largely dependent on the semen quality and insemination procedure. In practice, liquid semen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…To our knowledge, this is the first study to describe the differential expression of AQPs mRNA during liquid storage of boar AI doses at 17°C up to 48 hr. Our results showed a decrease in sperm total motility at 48 hr (72 hr after sample collection), in agreement with previous studies describing a decrease in the total motile spermatozoa after 72‐hr storage (De Ambrogi et al., 2006 ; Khoi et al., 2021 ). Although these authors did not find any differences in sperm membrane integrity, our results showed a decrease after 48‐hr incubation, agreeing with a previous study (Dubé et al., 2004 ).…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, this is the first study to describe the differential expression of AQPs mRNA during liquid storage of boar AI doses at 17°C up to 48 hr. Our results showed a decrease in sperm total motility at 48 hr (72 hr after sample collection), in agreement with previous studies describing a decrease in the total motile spermatozoa after 72‐hr storage (De Ambrogi et al., 2006 ; Khoi et al., 2021 ). Although these authors did not find any differences in sperm membrane integrity, our results showed a decrease after 48‐hr incubation, agreeing with a previous study (Dubé et al., 2004 ).…”
Section: Discussionsupporting
confidence: 93%
“…In fact, a limitation of bull semen is its lower amount of seminal plasma as compared to that in swine and equine species, which does not allow for the carrying out of more in-depth evaluations. Moreover, the fertility parameters considered and related to the OS in SP are also different between studies: sperm viability, morphology, motility, and DNA fragmentation are the most relevant assessment used to provide insight into spermatozoa quality and fertilizing ability [ 35 , 36 , 37 , 38 , 39 ]. As regards semen motility, the use of different settings and instruments should be taken into account when comparing with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The methods for directly measuring ROS level include chemiluminescence assays, static oxidation-reduction potential, and fluorescent probes such as dichlorodihydrofluorescein (H 2 DCFDA) [ 82 ]. Moreover, the total antioxidant capacity (TAC) in seminal plasma and the total ROS level also are important indicators reflecting the change of oxidative stress levels during the liquid storage of livestock semen [ 89 , 130 , 131 ]. Another important oxidative damage of sperm triggered by ROS is lipid peroxidation.…”
Section: Effects Of Extended Non-freezing Storage Of Human Spermatozo...mentioning
confidence: 99%